THE IMPLEMENTATION OF THE SPECIAL CURRICULUM OF ISLAMIC SD IN THE ESTABLISHMENT OF STUDENTS' RELIGIOUS ATTITUDES - Septian Arief Budiman; Fil Isnaeni; Donny Indradi (The University of Kuningan, 2022)
Education curriculum policies in Indonesia change with the times, curriculum changes will adapt to the needs of the community, especially in children's knowledge, attitudes and psychomotor, and one that is shifting in the direction of concern is the religious attitude of children at this time, this study aims to analyze the level of effectiveness curriculum that are applied at the Kamila Insan Cita Islamic Elementary School in the context of forming students' religious attitudes, this study uses a qualitative method with a field research approach where researchers manage data through interview documents and observations, interviews conducted are in accordance with applicable research methodology guidelines and in accordance with research needs. at the Kamila Insan Cita Islamic Elementary School which is located in Sawangan District, Depok City, West Java, the results of this study indicate that the level of effectiveness of curriculum implementation in the context of forming the religious attitudes of students in the fairly good category is evidenced by the results of interviews with researchers with a number of research objects such as school principals, teachers, parents of students.